FACTORS INFLUENCING STUDENT’S INTEREST IN BECOMING PUBLIC ACCOUNTANTS: CASE OF PRIVATE UNIVERSITY STUDENTS IN BOGOR - Meilita, Shelley; Lukman, Hendro (Graduate Program of Universitas Tarumanagara, 2024)
The increasing demand for graduate accounting students majoring in accounting cannot match Indonesia's high demand for public accountants. The profession of accountant is supposed to be one that offers a good prospect of employment because of its high demand. However, the exam to become a certified public accountant is quite difficult, and there are many career options to become an accountant in different fields. A wide job market with severe competition, among other factors, can push students to seek a career as an accountant. Thus, this study aims to look at the extent to which any factor can influence accounting students, in particular students of the private university in Bogor, in their careers as public accountants. Factors studied in this study include social environment, career motivation, and financial reward. The research population is the total number of active students at the private university in Bogor by 2023. The samples obtained are 166 active private university students in Bogor for 2021 and 2022. Data processing in this study uses the PLS-SEM method, multiple linear regression analysis, and hypothesis testing. The findings of this study demonstrate how the social environment, career motivation, and financial rewards affect students’ intentions when choosing careers as accountants. The implication of this research is that students should have a deep understanding of a career as a public accountant for the future of their career and the sustainability of this profession.